New analytical possibilities for monitoring the phase development during the production of autoclaved aerated concrete. (May 2018) - Schreiner, J.; Jansen, D.; Ectors, D.; Goetz-Neunhoeffer, F.; Neubauer, J.; Volkmann, S.
Abstract: This work presents improved analytical methods for both steps of the production process of autoclaved aerated concrete (AAC), the phase development during the hydration before autoclaving and during the autoclaving process itself. The improvement includes new insights into preparation methods of AAC samples for powder diffraction as well as Rietveld refinement strategies. For the first time a new implementation for calculating anisotropic crystal domain sizes is applied to major hydrate phases occurring during AAC production, namely portlandite during the hydration before autoclaving and tobermorite during the autoclaving process. The calculation of anisotropic domain size growth, which can be implemented in the Rietveld environment, is based on crystallographically and geometrically appropriate models. The implementation of calculating anisotropic domain sizes for the Rietveld software TOPAS 5.0 allows a superior Rietveld fit and a more accurate quantification of the phase development. Additionally it enables the tracking of growth mechanism of portlandite during hydration.